Apoptotic Induction and Cell-Cycle Arrest in Triple-Negative Breast Cancer Cells by Annona muricata Acetogenin Fractions: An In Silico and In Vitro Study - Lestini Wulansari; Leonardo Simanjuntak; Vania Delma (Eureka Herba Indonesia, 2025)
Triple-negative breast cancer (TNBC) is an aggressive molecular subtype that lacks oestrogen, progesterone and HER2 receptors and retains cytotoxic chemotherapy as its principal systemic option, creating a rationale for adjunctive phytotherapy. Annona muricata L. (Annonaceae), known in Indonesia as sirsak, contains Annonaceous acetogenins with well-documented mitochondrial and apoptotic activity. This study integrated molecular docking with in vitro pharmacology to characterise the anticancer effects of an HPLC-standardised acetogenin-enriched fraction (AEF) from Indonesian A. muricata leaves on TNBC cells. Annonacin, bullatacin, squamocin and muricatacin were docked against EGFR, Bcl-2, CDK2, caspase-3 and topoisomerase II-α (AutoDock Vina); AEF was tested on MDA-MB-231 and MDA-MB-468 TNBC cells with MCF-10A non-tumorigenic controls (n = 6 independent biological replicates per arm). Outcomes included viability (MTT), apoptosis (Annexin-V/PI), cell-cycle distribution (propidium iodide), caspase-3/7 luminescence, Western blotting (Bcl-2, Bax, cleaved caspase-3, cyclin D1, p21) and mitochondrial ΔΨm/ROS. Bullatacin showed the strongest binding to Bcl-2 (ΔG = −9.6 kcal/mol) and caspase-3 (ΔG = −8.9 kcal/mol). AEF inhibited MDA-MB-231 viability with IC50 12.4 µg/mL (95% CI 10.8–14.1) and yielded a selectivity index of 4.20 over MCF-10A. Apoptotic cells increased 4.62-fold, the G1 fraction rose from 41.2% to 64.8% (p < 0.001), caspase-3/7 activity rose 3.81-fold and the Bcl-2/Bax ratio decreased by 61%. In conclusion, bullatacin-rich Annona muricata acetogenins selectively induce intrinsic apoptosis and G1 arrest in TNBC cells, supporting their further translational development as Indonesian phytotherapeutic leads for hormone-refractory breast cancer.